Eddy Current Retarding PWM Controller Which Based upon CPLD - Minjin Xiao (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
A new kind of eddy current retarding PWM controller which used a complicated CPLD EPM7128SLC84-15 as main control unit has been designed in this paper.This design which built PWM controller in CPLD has realized output brake torque's stepless adjustment.The result of operation has shown that the kernel control circuit which used CPLD can meet traffic well. The whole system has high reliability and stability.